IMPLEMENTASI TEKNOLOGI PENGELOLAAN TANAMAN TERPADU (PTT) PADA USAHATANI PADI DI KABUPATEN CIANJUR - Agatha Kinanthi; Andriyono Kilat Adhi; Dwi Rachmina (Forum Agribisnis, 2014)
National rice production Enhancement Programme (P2BN) is one of Indonesia government effort to fulfill the need of national rice due to high consumption level of rice ( 102 kg. per capita per year ). On 2008 the program was implemented in a field school for integrated plant management (SLPTT). SLPTT was designed to increase farming productivity and its income usahatani and improve the farmers’ welfare. The study aimed to describe the implementation of integrated plant management technology (PTT Technology) and analyzing its effect to the paddy farming productivity and income of 40 paddy farmers (20 PTT farmers and 20 non-PTT farmers that was purposively choosen) in Sukaratu, Gekbrong, Cianjur. The result showed that the PTT technology implementation level in Sukaratu is still low, more than 50% of the farmers were applied only 4 out of 6 components of basic PTT technology and 2 out of 7 components of PTT technology. However, it was proved that the PTT technology improved the productivity, revenue, and the efficiency of paddy farming. The productivity of a SLPTT paddy farming (6 tonnes/ha) is higher than that of non-SLPTT paddy farming (5.13 tons/ha). The income of SLPTT paddy farming (Rp 9.382.641/ha) is larger than that of non-SLPTT farmer. Base on RC ratio, the SLPTT farmers (R/C 1.87) are more efficient than non-SLPTT farmer (R/C 1.66).